Dissociative electron attachment to chlorine dioxide probed by velocity slice im-aging. (August 2015) - Gope, Krishnendu; Prabhudesai, Vaibhav S; Mason, Nigel; Krishnakumar, E
Synopsis: We report the study of dissociative electron attachment (DEA) to chlorine dioxide (OClO) in the energy range of 1 to 10 eV using velocity slice imaging technique. DEA to OClO shows Cl −, O −, O2 −, and OCl − as fragment channels at various electron energies. Based on the momentum images of these ions we unravel the molecular dynamics leading to DEA.